Development of Psychometric Properties of Farmers' Occupational Health Behavior Questionnaire for Iranian Farmers. Issue 3 (2nd July 2020) - Moradhaseli, Somayeh; Farhadian, Homayoun; Colosio, Claudio; Abbasi, Enayat; Ghofranipour, Fazlollah
ABSTRACT: Background : Agriculture is one of the most dangerous industries throughout the world, and its risk level is dictated by several determinants whose real weights are often unknown. Objective : The present work aims to develop psychometric properties of farmers' occupational health behavior questionnaire for Iranian farmers. Methods : In this qualitative-quantitative study, the items of the instrument were derived from the qualitative phase. Face validity, content validity, reliability, and consistency methods were applied. Construct validity was estimated by the exploratory factor analysis. Results : Eleven factors with factor loads of >0.501 were extracted as the main factors. They altogether captured about 58.97% of the variance of factors affecting farmers' occupational health behavior. The reliability of the instrument was confirmed as its Cronbach's alpha was in the range of 0.72–0.93. Conclusion : Given the complicated nature of occupational health behaviors among farmers, it is imperative to measure the factors influencing these behaviors precisely. Therefore, the development of a proper instrument can be very crucial in identifying influential factors. The findings showed that the developed instrument was optimally reliable and valid.